Effect of co-doping process on topography, optical and electrical properties of ZnO nanostructured - Mohamed, Ruziana; Mamat, Mohamad Hafiz; Malek, Mohd Firdaus; Ismail, Ahmad Syakirin; Mohd Yusoff, Marmeezee; Syamsir, S. A.; Khusaimi, Zuraida; Mahmood, Mohamad Rusop (American Institute of Physics Inc., 2018)
We investigated of Undoped ZnO and Magnesium (Mg)-Aluminium (Al) co-doped Zinc Oxide (MAZO) nanostructured films were prepared by sol gel spin coating technique. The surface topography was analyzed using Atomic Force Microscopy (AFM). Based on the AFM results, Root Mean Square (RMS) of MAZO films have rougher surface compared to pure ZnO films. The optical and electrical properties of thin film samples were characterized using Uv-Vis spectroscopy and two point probes, current-voltage (I-V) measurements. The transmittance spectra for both thin samples was above 80% in the visible wavelength. The MAZO film shows the highest conductivity compared to pure ZnO films. This result indicates that the improvement of carrier mobility throughout doping process and possibly contribute by extra ion charge.